(untitled) (International Journal of Engineering and Computer Science, 2017)
with recent advance in web technology, many online shopping websites have been emerged. Despite its advantages, however, online shopping presents certain drawbacks. One drawback is that it may be difficult for a person to visualize how a given article would look if worn by that person-owing to the rich variation in body size and shape, hair and skin color, etc., in the human population. Testing the fitness of clothes is highly important for both customer and trader. Our approach concentrate on how the selected garment fitted the user’s body and how it will be appear as if he/she in real world. This was carried out by identifying critical points on garment and user’s body dimensions using image processing techniques. In this paper, an application for mitigating the virtual dressing room was designed, implemented and tested.